Determining the Factors Affecting Air Quality in Marmara, Turkey, and Assessing it Using Air Quality Indices - Ismet Yener; Kazım Onur Demirarslan (Doğal Afetler ve Çevre Dergisi)
Air pollution due to anthropogenic activities is currently one of the most important problems faced worldwide. This study aimed to determine the associations between air quality and spatial, meteorological, and anthropogenic factors while evaluating air quality using the air stress index (ASI) and the daily air quality (DAQx) scale. The annual mean levels of CO, NOx, O3, PM 2.5, PM10 and SO2 in the region were 718.6, 39.5, 44.4, 25.5, 51.3, and 9.9 μg/m3 , respectively. While anthropogenic variables mostly affected NOx (r=0.56 to 0.64) and O3 (r=-0.34 to 0.64), meteorological (r=-0.38 to 0.45) and spatial factors (r=-0.41 to -0.65) mostly affected particulate matter (PM2.5 and PM10). CO and SO2, on the other hand, were affected by all types of variables at varying directions and rates. The mean ASI and DAQx values of 2.1 and 4.3 indicated that the air quality in the region exhibited distinct air stress and sufficient air quality, respectively. The findings and outcomes could contribute to understanding and evaluating the air quality in the region and could be used as a base for further studies.